THE EFFECT OF BRAND AWARENESS, BRAND IMAGE, AND BRAND CREDIBILITY ON OPPO MOBILE PHONE BRAND PRODUCT PURCHASE INTENTION - Ryan Khrisnanda, Harjunan Rizky; Bayu Dirgantara, I Made (Diponegoro Journal of Management, 2021)
This study investigates about the impact of brand awareness, brand image, brand credibility to the mobile phone product purchase intention on Indonesian mobile phone market industry. This study proposes that brand awareness, brand image, brand credibility, significantly affect consumer purchase intention, focusing on several common mobile phone brand that exist and dominate the Indonesian market share mobile phone industry. This study also provides information about mobile phone consumer view on product brand to maintain the brand and raise the purchase intention of the product. A deductive, and quantitative research method using online self-completed questionnaire applied to a target sample of 100 people in Indonesia and domiciled on the Java island (East Java, Central Java, West Java, Banten, DI Yogyakarta, DKI Jakarta). The research adopts multiple regression analysis to examine and analyse the hypothesis related to the connection of brand awareness, brand credibility, and brand image, to purchase intention by data sample about the consumer perspective of mobile phone brand marketing quality on several common mobile phone brands in Indonesia, that be conducted to accomplish the research objectives which are: to fill the gap of research about consumer behaviour in Indonesia, to know the role of brand awareness, to understand the perception of Indonesian customer, to present the relation between brand awareness, brand image, and brand credibility to purchase intention. There are lot of research outside Indonesia that have a main point on brand loyalty that affect purchase intention within mobile phone industry. But unfortunately, there are just a few researches about the relation between the other factors apart from brand loyalty. Research found that the consumer purchase intention affected by its brand awareness, brand credibility, and brand image of the product